2016
DOI: 10.1016/j.ijnurstu.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between nurses’ empathy, self-compassion and dimensions of professional quality of life: A cross-sectional study

Abstract: Background: Job stress and burnout are common among healthcare professionals, and nurses in particular. In addition to the heavy workload and lack of recourses, nurses are also confronted with emotionally intense situations associated with illness and suffering, which require empathic abilities. Although empathy is one of the core values in nursing, if not properly balanced it can also have detrimental consequences, such as compassion fatigue. Self-compassion, on the other hand, has been shown to be a protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
213
9
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 275 publications
(261 citation statements)
references
References 64 publications
28
213
9
11
Order By: Relevance
“…Studies using the ProQOL questionnaire suggest that greater professional quality of life (more compassion satisfaction, and less burnout and compassion fatigue) is related to less depression and anxiety (e.g., Hegney et al, 2014;Yadollahi, Razmjooei, Jamali, Niakan, & Ghahramani, 2016), negative affect (e.g., Hegney, Rees, Eley, Osseiran-Moisson, & Francis, 2015;Zeidner, Hadar, Matthews, & Roberts, 2013), and perceived stress (e.g., Amin, Vankar, Nimbalkar, & Phatak, 2015), and greater general psychological and physical well-being (e.g., Mullira & Ssendikadiwa, 2016;Yadollahi et al, 2016), psychological resilience (Hegney et al, 2015), emotional intelligence, adaptive coping (Zeidner et al, 2013), mindfulness (e.g., Thomas & Otis, 2010), self-compassion (e.g., Duarte, Pinto-Gouveia, & Cruz, 2016), and empathy (e.g., Duarte et al, 2016;Gleichgerrcht & Decety, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using the ProQOL questionnaire suggest that greater professional quality of life (more compassion satisfaction, and less burnout and compassion fatigue) is related to less depression and anxiety (e.g., Hegney et al, 2014;Yadollahi, Razmjooei, Jamali, Niakan, & Ghahramani, 2016), negative affect (e.g., Hegney, Rees, Eley, Osseiran-Moisson, & Francis, 2015;Zeidner, Hadar, Matthews, & Roberts, 2013), and perceived stress (e.g., Amin, Vankar, Nimbalkar, & Phatak, 2015), and greater general psychological and physical well-being (e.g., Mullira & Ssendikadiwa, 2016;Yadollahi et al, 2016), psychological resilience (Hegney et al, 2015), emotional intelligence, adaptive coping (Zeidner et al, 2013), mindfulness (e.g., Thomas & Otis, 2010), self-compassion (e.g., Duarte, Pinto-Gouveia, & Cruz, 2016), and empathy (e.g., Duarte et al, 2016;Gleichgerrcht & Decety, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…A high level of perfectionism is associated with low levels of mindfulness [118] and a tendency to adopt ruminative and brooding thinking, which is a maladaptive coping strategy [119]. Individuals who over-identify and ruminate have a tendency to feel overwhelmed and carried away by their negative emotional thoughts and reactions [110]. In this study, nearly a third (30%) of the acute care nurses had low SCS scores on the Mindfulness subscale.…”
Section: Discussion Of Results In Relation To Self-compassionmentioning
confidence: 57%
“…A study by Duarte, Pinto-Gouveia and Cruz [110] suggests that being caring, supportive and understanding towards oneself (Self-Kindness -a characteristic associated with Self-Compassion), has the potential to be protective against CF. The results of this study indicated that acute medical care hospital nurses acknowledge that helpful thinking styles on duty at work include thinking realistically and putting things in perspective.…”
Section: Discussion Of Results In Relation To Self-compassionmentioning
confidence: 99%
“…En concreto, se ha expresado la preocupación por los efectos del estrés sobre la salud y el bienestar de los profesionales enfermeros (10,11). Entre los diversos problemas que caracterizan el entorno laboral de los enfermeros se han destacado factores como el bajo apoyo en las relaciones del trabajo, bajo control, necesidad continua de formación (12) y altas demandas del trabajo (11); ser trasladados a diferentes unidades clínicas de la organización, limitación de recursos, afrontar la muerte y excesiva carga de trabajo (13); rotación de turnos, demanda de tiempo (14); falta de control e implicación emocional (15); relaciones laborales ineficaces con los médicos (16); y pobres relaciones con los supervisores (17).…”
Section: Introductionunclassified